Expert Answers

An illustration of the letter 'A' in a speech bubbles

Let f(x) = cotx

Then we know that: cot x = cosx/sinx

==> f(x) = cosx/sinx

Let us differetiate using the chain rule:

f(x) = u/v   such that:

u= cosx  =-=> u' = -sin

v= sinx ==> v' = cosx

==> f'(x) = (u'v- uv')/v^2

                = (-sinx*sinx - cosx*cosx)/ sin^2 x

                  = (-sin^2x - cos^2x)/sin^2 x

Let us fctor -1 from the numerator:

==> f'(x) = -1(sin^2x + cos^2 x)/sin^2 x

We know that:

sin^2 x + cos^2 x = 1

==> f'(x) = -1/sin^2 x

But csc x = 1/sinx

==> f'(x) = - csc^2 x ...... q.e.d 

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial